Modeling and prediction of ice hockey match results - Patrice, M.; Sediva, B.; Toupal, T. (Journal of Quantitative Analysis in Sports, 2014)
Modeling and prediction of ice hockey match results are not as widely examined areas as modeling and prediction of association football match results. It is assumed that match results in football and ice hockey can be modeled by the bivariate Poisson distribution or by some modification of this distribution. The aim of this paper is to explore the possibility of using models derived for football match results also for ice hockey match results and to propose some modifications of these models. A new model based on alternative definition of the bivariate Poisson distribution is presented. The models are tested on historical data from the highest-level ice hockey league in the Czech Republic between the years 1999 and 2012.